2012
DOI: 10.1371/journal.ppat.1003014
|View full text |Cite
|
Sign up to set email alerts
|

Changes in JC Virus-Specific T Cell Responses during Natalizumab Treatment and in Natalizumab-Associated Progressive Multifocal Leukoencephalopathy

Abstract: Progressive multifocal leukoencephalopathy (PML) induced by JC virus (JCV) is a risk for natalizumab-treated multiple sclerosis (MS) patients. Here we characterize the JCV-specific T cell responses in healthy donors and natalizumab-treated MS patients to reveal functional differences that may account for the development of natalizumab-associated PML. CD4 and CD8 T cell responses specific for all JCV proteins were readily identified in MS patients and healthy volunteers. The magnitude and quality of responses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 41 publications
5
32
0
Order By: Relevance
“…NTZ was showed to disturb the balance between cytokines, up regulating some pro inflammatory cytokines 38 and decreasing the expression of the co-stimulatory molecule CD134 on CD4(+)CD26(HIGH) T-cells 39 . Also, Perkins and coworkers reported that patients receiving Natalizumab who developed PML do not present JCV-specific T cell response or had JCV-specific CD4 T cell responses uniquely dominated by IL-10 production 40 . Unfortunately, no immunological test was performed in the present study to confirm if this would be the case here.…”
Section: The Follow Upmentioning
confidence: 99%
“…NTZ was showed to disturb the balance between cytokines, up regulating some pro inflammatory cytokines 38 and decreasing the expression of the co-stimulatory molecule CD134 on CD4(+)CD26(HIGH) T-cells 39 . Also, Perkins and coworkers reported that patients receiving Natalizumab who developed PML do not present JCV-specific T cell response or had JCV-specific CD4 T cell responses uniquely dominated by IL-10 production 40 . Unfortunately, no immunological test was performed in the present study to confirm if this would be the case here.…”
Section: The Follow Upmentioning
confidence: 99%
“…Reduced expression of CD62L on CD4 + T cells in HIV-and natalizumab-associated PML might not only provide a novel biomarker for PML but points to an altered activation status of peripheral T cells before onset of PML (Schneider-Hohendorf et al, 2014;Schwab et al, 2013). Another study reported either no detectable JCV-specific T cell response or an aberrant JCV-specific T cell response dominated by production of anti-inflammatory IL-10, as well as higher levels of IL-10 in the CSF in MS patients with natalizumabassociated PML as opposed to MS patients without PML (Perkins et al, 2012). In HIV-associated PML patients, a…”
Section: Role Of Cd4 + T Cells In Pmlmentioning
confidence: 99%
“…Broad reactivity of CD4 + and CD8 + T cells against each of the JCV proteins was recognized in MS patients and healthy donors by using intracellular cytokine staining and flow cytometry after stimulation with 5 peptide pools, which contained overlapping 15-mer peptides with each peptide pool covering one of the viral proteins, i.e. agnoprotein, VP1, VP2, large T antigen and small t antigen (Perkins et al, 2012). In this study, different viral proteins were immunodominant in different donors and most donors showed reactivity of both CD4 + and CD8 + T cells.…”
Section: Antigen Specificitymentioning
confidence: 99%
“…The measure of JCV-specific T-cell responses directed against the JCV VP1 protein by quantification of interferon gamma production yielded conflicting results when examining longitudinal T-cell responses to JCV in individuals with MS treated with natalizumab (Chen et al, 2009;Jilek et al, 2010). Peripheral blood mononuclear cells of PML patients, when stimulated by anti-CD28 and anti-CD49d monoclonal antibodies, in the presence or absence of the Staphylococcus aureus enterotoxin B superantigen, did not show detectable T-cell responses to JCV, or had JCV-specific CD4 + T-cell responses uniquely dominated by IL-10 production rather than interferon gamma (Perkins et al, 2012). Thus, because the production of IL-10 by JCVspecific CD4 + T cells may interfere with this antiviral activity to the detriment of JCV replication control, either locally in the CNS or in peripheral tissues, becoming causative of PML, the authors proposed the measure of IL-10 for the identification of patient prone to develop PML.…”
Section: Il-10 Production By Cd4 + T Cellsmentioning
confidence: 99%